2007
DOI: 10.1021/la7010698
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying Hydrodynamic Slip:  A Comprehensive Analysis of Dewetting Profiles

Abstract: To characterize nontrivial boundary conditions of a liquid flowing past a solid, the slip length is commonly used as a measure. From the profile of a retracting liquid front (e.g., measured with atomic force microscopy), the slip length can be extracted with the help of a Stokes model for a thin liquid film dewetting from a solid substrate. Specifically, we use a lubrication model derived from the Stokes model for strong slippage and linearize the film profile around the flat, unperturbed film. For small slip … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
93
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(96 citation statements)
references
References 28 publications
3
93
0
Order By: Relevance
“…From the dynamics of hole growth 27,28,34-40 as well as from the shape of the liquid rim surrounding the hole one can get information about the slip or no-slip boundary condition of the liquid close to the solid substrate. 17,41,42 In the late stage, the straight ribbons that separate two coalescing holes decay into droplets due to the Rayleigh-Plateau instability, 43 c.f. Fig.…”
Section: Experimental Model Systems For Simple Liquidsmentioning
confidence: 99%
“…From the dynamics of hole growth 27,28,34-40 as well as from the shape of the liquid rim surrounding the hole one can get information about the slip or no-slip boundary condition of the liquid close to the solid substrate. 17,41,42 In the late stage, the straight ribbons that separate two coalescing holes decay into droplets due to the Rayleigh-Plateau instability, 43 c.f. Fig.…”
Section: Experimental Model Systems For Simple Liquidsmentioning
confidence: 99%
“…According to our previous studies on OTS and DTS concerning nonentangled PS melts, asymmetric rims are related to slippage [13][14][15]. For DTS, slip lengths b of up to 5 m were obtained, for OTS, values are about 1 order of magnitude smaller.…”
mentioning
confidence: 92%
“…These previous studies, however, lack one facet, which by now has been identified as one of the major issues influencing dewetting dynamics and profiles: hydrodynamic slippage [13][14][15]. In this Letter, we study the very nature of slippage in a molecular weight regime where chain entanglements can make an impact on the solidliquid interface friction.…”
mentioning
confidence: 95%
See 2 more Smart Citations